Integrated transcriptomic and metabolomic analyses reveal the mechanism by which quercetin inhibits reflux esophagitis in rats - Zheng Guo; Yanping Tang; Mingli Li; Lei Yang; Lei Liu; Peicai Li; Siyu Liu (PLoS ONE, 2025)
Quercetin relieved symptoms in rats with reflux esophagitis (RE), but the underlying mechanism remains unclear. Quercetin attenuated esophageal mucosal inflammation in RE rats by inhibiting the production of the inflammatory factors interleukin-1β (IL-1β) and interleukin-6 (IL-6). Additionally, through transcriptomic and metabolomic analysis, we found that metabolites related to bile acid metabolism, such as taurine, taurocholic acid, and nicotinamide, were closely associated with RE in rats. Quercetin reduced the expression of bile acid-related genes such as Cd38, seizure related 6 homolog like 2 (Sez6l2), and nitric oxide synthase 2 (Nos2), which may be characteristic genes and therapeutic targets for RE.